Evaluation of the Hardness of Cold Cured Acrylic Resin Material by Processing at Different Temperature - Rashid, Amal (Iraqi National Journal of Nursing Specialties, 2011)
Objective(s): This study aims to evaluate the hardness of two commercially available cold cured acrylic resin material (Vertex and PAN) when polymerized at different temperature in comparison to those polymerized by conventional methods in air at 23C ± 5C. Methodology: Eighty specimens, forty from cold cured acrylic (Vertex Type) and forty from cold cured acrylic (PAN type) were prepared, flasking and packing procedure were done according to manufacturer direction and divided according to processing as follow: 20 specimens (10 from Vertex type and 10 from PAN type) were processed in air for two hours at 23C ± 5C under press (bench curing) as a control, and 60 specimens (30 from Vertex type and 30 from PAN type) were processed by ivomat curing device containing water under air pressure 30 Pascal for 15 minutes at different temperature: 40C, 60C, and 80C (10 specimens for each groups). All specimens were tested for hardness test by shore D device. Results: Result showed that cold cured acrylic type PAN (polymerized by elevated temperature 80˚C) show the maximum value of hardness (88.696) followed by cold cured acrylic type vertex polymerized at 60˚C (88.471). While, control group type PAN (polymerized at air bench) recorded the minimum value of hardness (81.83). All groups that polymerized at high temperature: 40C, 60C, and 80C show the higher value of hardness in comparison to those processed by conventional methods (at air bench) with significant and highly significant differences. Recommendations: Studies need to study the effect of increasing time and pressure of curing process on the hardness of cold cure acrylic material, also to study the effect of increasing temperature of curing on the other properties of cold cure acrylic material.